Science and the Building of a New Japan - Low, M. author. aut Link
XIV, 259 p. 11 illus.
Keywords: This book highlights the importance of individuals in the shaping of postwar Japan by providing an historical account of how physicists constituted an influential elite. An history of science perspective provides insight into their role, helping us to understand the hybrid identity of Japanese scientists, and how they reinvented not only themselves, but also Japan. The book is special in that it uses the history of science to deal with issues relating to Japanese identity, and how it was transformed in the decades after Japan's defeat. It explores the lives and work of seven physicists, two of whom were Nobel prize winners. It makes use of little-known Occupation period documents, personal papers of physicists, and Japanese language source material.